Implementasi Hak dan Kewajiban Istri Bagi Wanita Karir di Kantor Kementerian Agama Kota Lubuklinggau Menurut Undang-Undang Perkawinan 1974 dan Kompilasi Hukum Islam(Analisis Normatif-Sosiologis) - Ma’rufah, Lilis; Yusefri, Yusefri; Saputra, Hasep (STAI Bumi Silampari, 2022)
This study focuses on discussing the Islamic view of career women, and the implementation of the rights and obligations of wives for career women of female state civil servants, at the Ministry of Religion Office of Lubuklinggau City. The spectrum that is highlighted, of course, explores the position of Career Women, whether they can carry out their obligations in a balanced way, both as wives and as ASN employees. This study uses sociological normative analysis. This normative analysis uses a study approach that examines a problem that arises by referring to religious benchmarks. In this study, the author also refers to the Marriage Law in Indonesia and the Compilation of Islamic Law. The findings in this study indicate that the wife's next obligation is to organize and manage daily household needs as well as possible. From the data above, the wife's responsibilities as stated in the Compilation of Islamic Law in Indonesia for wives who have the status of ASN at the Ministry of Religion of the City of Lubuklinggau have not been implemented properly. The wife has not fully done household chores, starting from taking care of the house, shopping for the house, cooking, or arranging the entire layout of the house is not fully done by the wife, but still involves household assistants and most of them cooperate with each other in household chores, both in terms of household chores. raising children, educating or doing housework